Fostering students' scientific and religious literacy through STREM-based transformative learning - Pribadi, Pandu; Susanti, Ani (International Journal on Education Insight, 2025)
This study aims to examine the effectiveness of STREM-based learning in enhancing the students’ scientific and religious literacy in the Basic Natural Science course. STREM – which refers to science, technology, religion, engineering, and mathematics – was used to teach 30 second-year-students of Islamic Education study program at STIT Muhammadiyah Banjar – a private teacher training school in Indonesia. Adopting the mixed-method approach, we used the pre-test and post-test to collect the quantitative data, while the qualitative data were gathered through interviews, observations, and student reflections. The results showed significant improvements in students’ scientific literacy (scored from 62.35 to 78.20) and religious literacy (scored from 58.10 to 74.65). Thematic analysis revealed that STREM-based learning could foster students’ critical thinking and encouraged deep spiritual reflection by linking scientific content with Islamic values. The integration of science and religion created a transformative learning experience, making the course more engaging and meaningful. These findings suggest that the STREM approach can serve as an effective model in Islamic higher education to develop holistic student competencies.